2015
DOI: 10.1155/2015/165908
|View full text |Cite|
|
Sign up to set email alerts
|

Patient-Specific CT-Based Instrumentation versus Conventional Instrumentation in Total Knee Arthroplasty: A Prospective Randomized Controlled Study on Clinical Outcomes and In-Hospital Data

Abstract: Total knee arthroplasty (TKA) is a frequently performed procedure in orthopaedic surgery. Recently, patient-specific instrumentation was introduced to facilitate correct positioning of implants. The aim of this study was to compare the early clinical results of TKA performed with patient-specific CT-based instrumentation and conventional technique. A prospective, randomized controlled trial on 112 patients was performed between January 2011 and December 2011. A group of 112 patients who met the inclusion and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…In total, eight studies [12][13][14][15][16][17][18][19] were included reporting a total of 828 knees (five RCTs [12][13][14][15][16] and three prospective comparative [17][18][19] ). Two series were extracted from the study by Pfitzner et al 14 as this had three arms investigating conventional versus PSI (CT) versus PSI (MRI).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, eight studies [12][13][14][15][16][17][18][19] were included reporting a total of 828 knees (five RCTs [12][13][14][15][16] and three prospective comparative [17][18][19] ). Two series were extracted from the study by Pfitzner et al 14 as this had three arms investigating conventional versus PSI (CT) versus PSI (MRI).…”
Section: Resultsmentioning
confidence: 99%
“…Maximum postoperative follow-up ranged between 3 months 12-14 in three studies and 2 years in two studies, 17,18 the remaining studies were either 6 15,19 or 12 months. 16 Six studies examined postoperative alignment parameters in addition to functional outcomes. [12][13][14][15]17,19 All eight studies reported postoperative KSS (function), [12][13][14][15][16][17][18][19] and seven studies reported KSS (knee).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations